Multi-physics analysis of electromagnetic forming process using an edge-based smoothed finite element method. (December 2017) - Li, She; Cui, Xiangyang; Li, Guangyao
Highlights: A edge-based smoothed finite element method for electromagnetic forming analysis is proposed. The Smoothed Galerkin Weak forms are presented in both electromagnetic and mechanical field. Transient eddy current and nonlinear dynamic analysis are implemented by present ES-FEM. The present method is feasible in solving electromagnetic forming problems. Abstract: In this paper, a coupled modelling of the electromagnetic field and the mechanical field based on edge-based smoothed finite element method (ES-FEM) is performed to investigate the electromagnetic forming (EMF) with large deformation. EMF technique is one of the high-speed forming methods, which including the transient eddy current and nonlinear dynamic analysis. In this work, Smoothed Galerkin Weak forms are presented in both electromagnetic and mechanical field, and numerical calculation framework for analysis of EMF process is established. The feasibility of present modelling is validated by a tube expansion example, the numerical result agrees well with the experimental one. The influences of system parameters, such as discharge voltage, frequency of current, are studied in the calculation of electromagnetic forming process. An optimum frequency that produces the maximum workpiece deformation for a given initial stored energy can be found using the present modelling. The present coupled modelling is useful for predicting deformation, and can be served as a guide to control EMF process design. Graphical abstract: In EMF process, the workpiece can be reshaped without any contact from a tool. The Lorentz force, which is generated by the electrical current induced in the workpiece by a coil, is controlled to deform the workpiece as displacement is controlled in conventional stamping process.